Challenges and issues in ski jumping biomechanics - Schwameder, H. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Ski jumping is a challenging and fascinating sport attracting large numbers of spectators during competitions both live on site and on television. Since its initiation, ski jumping has developed and improved continuously regarding technique, material and competition regulations. One of the most significant improvements has been the advent of the V flight technique in the late 1980's. Ski jumping entails enormous organizational demands and requires an extensive infrastructure. Thus, the number of runs possible during hill training is limited. Moreover, both flight and landing are considered high risk. These aspects may account for the relatively long history of biomechanics research primarily focusing on performance enhancement, limiting factors of the take-off, specific training and conditioning, aerodynamics, and safety. Due to the competitive nature of ski jumping, it can be assumed that only a limited number of the biomechanical studies which are conducted are in fact published. Consequently, the understanding and knowledge about ski jumping biomechanics might be considerably wider in specialised research groups compared to the information provided in the literature. The long distances covered during ski jumps present significant challenges for biomechanics research, specifically in field measurements and during competitions. Nevertheless, the biomechanics research findings substantially helped to increase the understanding of relevant mechanical and biological issues, performance enhancement, equipment improvement, safety and the development of regulations.